WSDLUD: a metric to measure the understanding degree of WSDL descriptions - Berón, Mario (2016)
In this article, WSDL Understanding Degree (WSDLUD) a metric aimed at measuring a priori the understandability of WSDL (Web Services Description Language) descriptions is presented. In order to compute WSDLUD, all the static information available in a WSDL description is collected. This information is submitted to an evaluation process based on a method named LSP (Logic Scoring of Preference). This evaluation process outputs a Global Preference value that indicates the satisfaction level of the WSDL description regarding the evaluation focus, in this case, the understanding degree.